2006
DOI: 10.1590/s1984-92302006000400002
|View full text |Cite
|
Sign up to set email alerts
|

Planejamento estratégico e gestão feminina em pequenas empresas: o caso das escolas particulares em Curitiba - Paraná

Abstract: RESUMO estudo teve como objetivos delinear o perfil das dirigentes e analisar o planejamento estratégico nessas empresas. Inicialmente foi desenvolvida revisão bibliográfica, abrangendo empreendedorismo, gênero feminino e planejamento estratégico em pequenas empresas. Para a pesquisa empírica, foi realizada uma parceria com o Sindicato das Escolas Particulares do Paraná, por meio da qual se ofertou um curso de planejamento estratégico para organizações escolares. Em função dessas características, o método de p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 1 publication
1
4
0
2
Order By: Relevance
“…However, this does not mean that such conflicts were eliminated, as the entrepreneurs pointed out that conflicts can occur at any time, which can result in momentary loss of this self control. Just as in Takahashi et al (2006) and Strobino (2009), most of the female entrepreneurs reported that they like what they do, corroborating Jonathan's (2003) research in the educational sector. Zampier et al (2011), in a study on the female gender, found that there is a great dedication to work.…”
Section: Professors and Gendersupporting
confidence: 79%
“…However, this does not mean that such conflicts were eliminated, as the entrepreneurs pointed out that conflicts can occur at any time, which can result in momentary loss of this self control. Just as in Takahashi et al (2006) and Strobino (2009), most of the female entrepreneurs reported that they like what they do, corroborating Jonathan's (2003) research in the educational sector. Zampier et al (2011), in a study on the female gender, found that there is a great dedication to work.…”
Section: Professors and Gendersupporting
confidence: 79%
“…Therefore, female entrepreneurship is the involvement of women in decisionmaking and business management (Hapsari & Soeditianingrum, 2018). According to Takahashi et al (2006), the best female entrepreneurs are between 35 and 50 years old, married, mothers, with a high level of education who invest little in social capital and choose to create small businesses.…”
Section: Female Entrepreneurshipmentioning
confidence: 99%
“…According to Welsch (1996), managing a company or educational institution involves decision-making, application of certain techniques, procedures, and motivation of individuals or groups towards achieving specific objectives. In this context, it is the managers' function to elaborate the organizational planning, using previous experiences in the organization, market researches, investigations, statistics, and inferences from research, among others (REZENDE, 2003).…”
Section: Introductionmentioning
confidence: 99%